Seed aid for seed security: advice for practitioners - International Center for Tropical Agriculture; Catholic Relief Services; CARE Norway (2012)
No. 2 presents an overview of the Country Case Studies undertaken to guide the design of the tools presented in Briefs 8 to 10 as well as to examine the effects of different types of interventions. The case studies were undertaken in Burundi, Ethiopia, Kenya, Malawi, Mozambique, Uganda and Zimbabwe. No. 3 introduces the general concept of seed security and differentiates parameters of availability, access, and seed and variety quality, as well as distinguishing chronic from acute stress. Briefs 4 and 5 consider focused topics that cut across seed assistance and seed security. No. 4 addresses issues of relief and agobiodiversity: the importance of diversity in stabilizing systems and the possible effects of various relief approaches in maintaining, enhancing, or undermining such diversity. No. 5 focuses on the opportunities and risks of using seed aid to move beyond the status quo ante by introducing seed of new varieties (or indeed, new crops altogether). Briefs 6 and 7 present short overviews of practice. No. 6 looks at the range of seed systems routinely used by small farmers in Africa and highlights the escalating importance of local markets . Effective interventions depend on a solid understanding of such standard seed procurement practices. No. 7 sketches the current major seed- system based response options , and reflects on their appropriateness in relation to the stresses on hand. The last set of briefs focus on tools and guidance. No. 8 examines how effective interventions depend on sound and timely assessment, which requires both a tool to assess seed system security and the knowledge and skill to use it. No. 9 starts to bring the cycle to a close by giving guidance on evaluating seed-aid projects , suggesting the types of evaluation needed and their content. The final brief then looks to the future and suggests a checklist for the development of proposals for seed assistance . It is this last which builds on the range of lessons learned.